Research progress on the intervention of mobile health Apps in the health management of cancer patients (移动健康APP在癌症患者健康管理干预中的研究进展) - WANG Tian (王田); LI Juan (李娟); MEI Yafan (梅亚凡) (Association of Integrative Nursing, 2023)
Cancers are of different nature and types, involving different tissues and organs, and are the most common cause of death in humans, seriously affecting the quality of life of patients. Mobile health is to make full use of mobile Internet communication technology to provide health butler services such as physical examination, health care, disease assessment, medical treatment, and rehabilitation. In foreign countries, the mobile health APP business has developed rapidly. Europe, the United States, Japan, and other countries, as well as my country's Taiwan region, have entered the stage of refined service. Mobile health Apps can effectively improve the utilization efficiency of medical resources and reduce the medical investment of beneficiaries. This article summarizes the relevant overview, application forms, effects, and deficiencies of the Internet at home and abroad in the health management of cancer patients. Therefore, the mobile health APP can play a greater role in the health of cancer populations in my country. (癌症性质类型各异, 累及不同组织和器官, 是人类最常见死因, 严重影响患者生存质量。移动健康是充分利用移动互联网通信技术来提供体检、保健、疾病评估、医疗、康复等健康管家服务。本研究介绍了移动健康APP的相关概念、移动健康APP发展现状, 阐述移动健康APP在癌症患者中的作用, 旨在为移动健康APP在我国癌症患者的应用提供参考依据。)